The comparison of strength, power and flexibility between on-road cyclist and off-road cyclist / Nurul Naemah Zulkuflly - Zulkuflly, Nurul Naemah (Faculty of Sport Science and Recreation, 2018)
Cycling is a sports activity that requires strength, power and flexibility. The objective of this study is to measure and compare the leg strength, leg power and the flexibility among the on-road cyclist and off-road cyclist. 20 cyclist has involves in this study (N=10) from on-road cyclist and (N=1O) from off-road cyclist. Subjects performed the lRM leg press test to measure strength, vertex pole vertical jump to measure power and sit and reach to measure flexibility. Data analysis was analysed using the independent t-test. The results show there was no significance difference on strength, power and flexibility between on road and off-road cyclist because of the p>0.05. However, the results show there is slightly difference between on-road and off-road cyclist based on the indicators it is because of the nature of the sports. As conclusion, to have a better performance of cycling, athletes should be trained specifically according to the fundamentals of the sports. The developments of fundamentals for on-road and off-road cycling events are important in order to have a better cyclist in the future.